Storage Equipment for Woodstock Assembly Line (Borneo Engineering & Advanced Multidisciplinary International Journal, 2023)
This addition storage design proposal aims to improve the efficiency of the Woodstock production line by reducing cycle times through the implementation of new storage equipment and material handling systems. The current process is plagued by delays and inefficiencies in material handling, leading to longer cycle times and reduced productivity. The proposed design is expected to reduce cycle times by up to 10%, resulting in increased productivity and cost savings. In the proposed design for storage equipment and material handling, worker safety is of utmost importance. The use of tin shoulder, scissor, and air pressure gun can pose potential hazards to workers if not properly managed. Therefore, the design will incorporate several safety features to mitigate any risks. Overall, the new storage and material handling system will help the Woodstock production line remain competitive in the market and better serve customer demands.